Prevalence of Poor Sleep Quality in Patients With Hypertension in China: A Meta-analysis of Comparative Studies and Epidemiological Surveys - Li, Lin; Li, Lu; Chai, Jing-Xin; Xiao, Le; Ng, Chee H.; Ungvari, Gabor S.; Xiang, Yu-Tao (Frontiers in Psychiatry, 2020)
Objective: This meta-analysis examined the prevalence of poor sleep quality and its associated factors in patients with hypertension in China. Methods: Both English (PubMed, PsycINFO, EMBASE) and Chinese (Wan Fang Database and Chinese National Knowledge Infrastructure) databases were systematically and independently searched. The random-effects model was used to estimate the prevalence of poor sleep quality in Chinese patients with hypertension. The funnel plot and Egger’s tests were used to assess publication bias. Results: The prevalence of poor sleep quality in 24 studies with 13,920 hypertensive patients was 52.5% (95% confidence interval (CI): 46.1%-58.9%). In contrast, the prevalence of poor sleep quality in 6 studies with 5,610 healthy control subjects was 32.5% (95% CI: 19.0%-49.7%). In these studies, compared to healthy controls, the pooled odds ratio (OR) of poor sleep quality was 2.66 (95% CI: 1.80-3.93) for hypertensive patients. Subgroup and meta-regression analyses revealed that hospital patients were more likely to have poor sleep quality than patients in the community. In meta-regression analyses, poor sleep quality was more common in male hypertensive patients, older patients and studies with smaller sample size and published in Chinese also reported higher prevalence. Conclusion: Appropriate strategies for screening, prevention and treatment of poor sleep quality in this population should be developed.